New thiazolidine-2,4-diones as potential anticancer agents and apoptotic inducers targeting VEGFR-2 kinase: Design, synthesis, in silico and in vitro studies - Elkady, Hazem; Mahdy, Hazem A.; Taghour, Mohammed S.; Dahab, Mohammed A.; Elwan, Alaa; Hagras, Mohamed; Hussein, Mona H.; Ibrahim, Ibrahim M.; Husein, Dalal Z.; Elkaeed, Eslam B.; Alsfouk, Aisha A.; Metwaly, Ahmed M.; et al. (Biochimica et biophysica acta. General subjects, 2024)
VEGFR-2 has emerged as a prominent positive regulator of cancer progression. Discovery of new anticancer agents and apoptotic inducers targeting VEGFR-2. Design and synthesis of new thiazolidine-2,4-diones followed by extensive in vitro studies, including VEGFR-2 inhibition assay, MTT assay, apoptosis analysis, and cell migration assay. In silico investigations including docking, MD simulations, ADMET, toxicity, and DFT studies were performed. Compound 15 showed the strongest VEGFR-2 inhibitory activity with an IC50 value of 0.066 μM. Additionally, most of the synthesized compounds showed anti-proliferative activity against HepG2 and MCF-7 cancer cell lines at the micromolar range with IC50 values ranging from 0.04 to 4.71 μM, relative to sorafenib (IC50 = 2.24 ± 0.06 and 3.17 ± 0.01 μM against HepG2 and MCF-7, respectively). Also, compound 15 showed selectivity indices of 1.36 and 2.08 against HepG2 and MCF-7, respectively. Furthermore, compound 15 showed a significant apoptotic effect and arrested the cell cycle of MCF-7 cells at the S phase. Moreover, compound 15 had a significant inhibitory effect on the ability of MCF-7 cells to heal from. Docking studies revealed that the synthesized thiazolidine-2,4-diones have a binding pattern approaching sorafenib. MD simulations indicated the stability of compound 15 in the active pocket of VEGFR-2 for 200 ns. ADMET and toxicity studies indicated an acceptable pharmacokinetic profile. DFT studies confirmed the ability of compound 15 to interact with VEGFR-2. Compound 15 has promising anticancer activity targeting VEGFR-2 with significant activity as an apoptosis inducer. •New VEGFR-2 inhibitors based on thiazolidine-2,4-diones have been designed and synthesized.•Anti-proliferative and VEGFR-2 inhibitory activity were tested.•Cell cycle and apoptosis analyses were assessed.•In silico docking, MD simulation, DFT, ADMET, and toxicity studies were performed.